2007
DOI: 10.1176/ps.2007.58.3.335
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Profiles of Patients Who Make Multiple Visits to Psychiatric Emergency Services

Abstract: Most visits to the psychiatric emergency service were made by frequent users who had distinctive profiles, which are potentially useful for developing clinical strategies to reduce the impact of this patient group on this service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 36 publications
4
32
2
1
Order By: Relevance
“…However, this is consistent with findings in most previous studies on the behavioral model's ability to predict service use [12,13]. In addition, the study did not include the full spectrum of psychiatric disorders such as schizophrenia which may account for a greater utilization of resources, especially specialized care [26].…”
Section: Discussionsupporting
confidence: 87%
“…However, this is consistent with findings in most previous studies on the behavioral model's ability to predict service use [12,13]. In addition, the study did not include the full spectrum of psychiatric disorders such as schizophrenia which may account for a greater utilization of resources, especially specialized care [26].…”
Section: Discussionsupporting
confidence: 87%
“…These findings are similar to those of Pasic et al 5 We also found that frequent attenders had longer psychiatric histories, higher rates of schizophrenia, and were more likely to be prescribed antipsychotics, but had equal gender distribution as compared with single attenders. Chaput & Lebel 6 reported similar findings in their study of similar patient population.…”
Section: Discussionsupporting
confidence: 69%
“…3 Well-developed community-oriented strategies, such as modified intensive case management and outreach programmes, which have been shown to reduce the heavy use of psychiatric in-patient services, 8 could also help limit frequent attenders' visits by reducing social instability and increasing treatment adherence. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Overcrowding in emergency departments (EDs) has become an issue of increasing concern in many jurisdictions [1,2], with repeated visits to the ED contributing to this phenomenon [1,3,4]. Many studies have shown that a relatively small group of patients account for a disproportionate number of ED visits [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%